The Public Interior Space Within Louvre Abu Dhabi Dome: A Visual Reflection - Musfy, Karim; Sosa, Marco; Ahmad, Lina (Interiority, 2021)
What defines an interior space? Is a traditional threshold the only building element considered as a clear component demarcating interiority from the outside environment? Could light or water be just as clear? How can scale challenge the identification of an internal space? Is a living space more identifiable as an interior volume? What about an internal courtyard for a family house outlining the beginning of a nation or the opposite extreme in the time-space continuum, a 24,000 square meters domed roof over a series of intimate spaces establishing a nation’s cultural intention internationally? Can a central space act as a gravitational point to other space fragments and elements? Can the ephemerality of the space bind it together in a unique, memorable encounter? We set ourselves to answer these questions using different phenomenological responses methods including digital video, photography, drawings, and architectural observations. All depict different layered trajectories through the segments of the architectural strata that compose a cultural enclosure, such as Jean Nouvel’s Louvre Abu Dhabi. As we transverses through space and time, we use regional typologies to create a timeline spectrum connecting regional context, culture and architecture, attempting to emphasise the interiority qualities of the space under the dome.